Dear peace - Lapira, Kris Brown Norman; Datumanong, Diagandhi (Communication Foundation for Asia, 2007)
A half-hour documentary on the unique peace communication process involving Christian and Muslim high school students who forged friendships and reconciliation after participating in a Peace Camp and workshops organized by CFA.